Management of Pre-eclampsia and Eclampsia: A Simulation - Cynthia Abraham; Natalya Kusheleva (Association of American Medical Colleges, 2019)
Introduction Pre-eclampsia is a hypertensive disorder in pregnancy. Maternal sequelae that may occur include impaired liver function, disseminated intravascular coagulation, seizures (eclampsia), stroke, and death. Thus, providers should know how to recognize (diagnose) and treat pre-eclampsia and eclampsia. Methods A simulator with noninvasive blood pressure monitoring was used. Transducers for fetal heart rate and contraction monitoring were placed on the simulator, which represented the patient. After obtaining a history and performing a physical examination, resident physician (postgraduate years 1-4) and nurse learners had to diagnose pre-eclampsia and treat this condition. They also had to treat severe-range blood pressures and manage eclampsia. Learner performance was assessed with a checklist. Debriefing followed the simulation. Results Thirty resident learners participated in the study. Nurses did not participate. All resident learners indicated familiarity with the diagnosis and management of pre-eclampsia and emergent hypertension and managed these conditions correctly. All resident learners reported not being confident in managing eclampsia. None of the learners were able to stop the eclamptic seizure. All resident learners were more confident in managing eclampsia after the scenario compared with before (mean confidence level 3.6 ± 0.5 vs. 1.1 ± 0.4, p < .001). Discussion Resident learners were familiar with the management of pre-eclampsia and emergent hypertension but not with eclampsia. We recommend that eclampsia simulations occur in a laboratory and in situ on the labor and delivery floor with interprofessional team members including obstetricians, nurses, anesthesiologists, emergency and family medicine physicians, nurse practitioners, and physician assistants.